Fluorine and phosphorus atoms cooperated on an N-doped 3D porous carbon network for enhanced ORR performance toward the zinc–air batteries. Issue 16 (5th April 2023) - Li, Mengwei; Ye, Qilong; Hou, Sanying; Yang, Jinlin; Chi, Bin; Deng, Yijie; Tian, Xinlong
Abstract : A three-dimensional N-doped porous carbon nanosheet catalyst cooperated by fluorine and phosphorus atoms was prepared in this work, which showed high oxygen reduction performance in 0.1 M KOH and a power density of 138 mW cm −2 in zinc–air battery. Abstract : The rational design of low-cost and high-efficiency N-doped porous carbon electrocatalysts for oxygen reduction reaction via a heteroatom doping strategy is pivotal to promoting the commercialization of fuel cells. Herein, we have developed a facile and efficient strategy to prepare a nitrogen-doped carbon network coupled with fluorine and phosphorus atoms by pyrolyzing the mixture of poly3-fluoroaniline coating g-C3 N4 with phytic acid. The prepared F/P–N–C-950 catalyst is featured by three-dimensional porous layered architecture, high specific surface area, and abundant high active sites from the synergistic effects between F, P, and N, and showed distinguished oxygen reduction performance with half-wave potential ( E 1/2 ) of 0.848 VRHE (exceeding that of commercial Pt/C) and long-term stability (94%). In the homemade zinc–air battery with F/P–N–C-950 as the cathode, it achieved a high peak power density (138 mW cm −2 ), promising specific capacity (821 mA h g −1 ), and good multiplicative stability.